2013
DOI: 10.1016/j.bbamem.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Lipid–protein nanodiscs promote in vitro folding of transmembrane domains of multi-helical and multimeric membrane proteins

Abstract: Production of helical integral membrane proteins (IMPs) in a folded state is a necessary prerequisite for their functional and structural studies. In many cases large-scale expression of IMPs in cell-based and cell-free systems results in misfolded proteins, which should be refolded in vitro. Here using examples of the bacteriorhodopsin ESR from Exiguobacterium sibiricum and full-length homotetrameric K(+) channel KcsA from Streptomyces lividans we found that the efficient in vitro folding of the transmembrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…Bicelles of a certain composition (DMPC/CHAPS, in this study) can be used, but their applicability is limited to a very narrow and uncomfortable range of protein and lipid concentrations. This presents a nice prospect for the use of LPNs as a membrane mimetic for structural studies of multidomain membrane proteins, especially since LPNs have been shown to be a perfect medium for the refolding of membrane proteins (32). Nanodiscs were first proposed as a reference medium for detergent screening (28) or as a possible environment in which to study the topology of small peptides in the membrane (33)(34)(35)(36); however, recent advances, such as the development of new MSPs that form smaller discoid particles (up to~50 kDa) (31), isotope labeling strategies, and NMR experimental techniques have also made them applicable for structural studies of membrane proteins (37).…”
Section: Nanodiscs As a Versatile Medium For Structural And Functionamentioning
confidence: 97%
“…Bicelles of a certain composition (DMPC/CHAPS, in this study) can be used, but their applicability is limited to a very narrow and uncomfortable range of protein and lipid concentrations. This presents a nice prospect for the use of LPNs as a membrane mimetic for structural studies of multidomain membrane proteins, especially since LPNs have been shown to be a perfect medium for the refolding of membrane proteins (32). Nanodiscs were first proposed as a reference medium for detergent screening (28) or as a possible environment in which to study the topology of small peptides in the membrane (33)(34)(35)(36); however, recent advances, such as the development of new MSPs that form smaller discoid particles (up to~50 kDa) (31), isotope labeling strategies, and NMR experimental techniques have also made them applicable for structural studies of membrane proteins (37).…”
Section: Nanodiscs As a Versatile Medium For Structural And Functionamentioning
confidence: 97%
“…LPNs, formed by a membrane scaffold protein (MSP), and lipids, contain a large patch of lipid bilayer and represent an almost ideal model of cellular membrane 12 . However, the size of LPNs is far too large for the solution NMR spectroscopy (~120-150 kDa), restricting their usage to application as a reference medium in the detergent screening and as an environment for the protein refolding [13][14][15] . Recent advances, such as modified MSPs, which provide smaller LPNs 16 , allow even the structural studies 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Although most suitable for solution NMR studies of integral helical membrane proteins (Gautier and Nietlispach , 2012 ), detergent/ phospholipid micelles provide a fairly unstable environment for GPCRs because of the constant exchange of the detergent molecules between their monomeric and micellar form, and the denaturing properties of detergents at high concentrations (Warschawski et al , 2011 ;Serebryany et al , 2012 ;Shenkarev et al , 2012 ). In addition, a fact that has often been neglected is the formation of non-native disulfide bonds between free cysteines.…”
Section: Discussionmentioning
confidence: 99%